A qualitative investigation into the patient-centered goal-setting practices of allied health clinicians working in rehabilitation. (June 2018) - Cameron, Lisa J; Somerville, Lisa M; Naismith, Catherine E; Watterson, Dina; Maric, Valentina; Lannin, Natasha A
Objective: To explore the ways clinicians engage rehabilitation patients in patient-centered goal setting and identify factors influencing the goal-setting process. Design: Ethnographic study utilizing observed practice—thematic analysis. Setting: Four rehabilitation wards of a large metropolitan hospital in Melbourne, Australia. Subjects: Participants included 17 rehabilitation patients, 18 allied health clinicians and one family member. Disciplines represented were speech pathology, occupational therapy, social work and physiotherapy. Method: Multiple qualitative methods were used. A total of 18 routine goal-setting interviews between clinicians and patients were audio recorded and transcribed. Together with associated entries in the patient medical record, transcripts were coded and developed into themes using thematic analysis. Finally, focus groups with clinicians were conducted to validate themes identified. Results: Three themes were identified describing factors which influence patient centeredness: "a goal-setting collaboration"—the interpersonal exchange between client and clinician; "the environment"—physical, temporal and structural; and "clinician self-awareness"—clinicians' insight into the ways they influence goal setting. The practice of patient-centered goal setting varied considerably between clinicians. Goals developed were strongly influenced by the clinician's views, although strategies of respect for the patient and reflective listening skills increased patient participation and the patient centeredness of goals developed. Conclusion: Goals developed with rehabilitation patients are more likely to be patient-centered when the interaction encourages the patient to express their needs and preferences, and these are heard by the clinician. For this to influence treatment, it must occur in an environment structured to support and value patient-centered goals.